Avaliação teórica e experimental do uso de resíduos siderúrgicos na sinterização - Victor Freire de Oliveira (2018)
The quality of worldwide iron ore sources has been changing in the past years, forcing raw materials with lower iron contents to be used in steelmaking. In parallel, environmental legislations throughout the world are becoming progressively more restrictive, which limits the amount of residues that can be landfilled or stored, besides demanding specific destinations for these materials. In light of this context, the usage of iron-bearing residues has been studied as an alternative for reaching advantageous results in all these spheres and for supplying sinter with proper quality for blast furnace ironmaking. For that to be possible, it is necessary to verify the behavior of metallurgic residues in the thermodynamic and kinetic conditions of the sintering process as well as their effects on sinter quality and sintering process parameters. With this goal, samples of typical Brazilian sinter plant raw materials were obtained and characterized (sinter feed, limestone, lime, dolomite, blast furnace dust, blast furnace sludge, BOF dust and fine BOF sludge). Mixes with various residue contents were prepared and submitted to high temperature tests in a tubular resistive furnace were performed. The chemical analysis and mineral phases results were confronted with the predictions of a multicomponent thermodynamic equilibrium model, aiming also at the validation of the latter. The results demonstrated that recycling 100% of the typical generation of the residues of an integrated steel mill does not add up to more than 4,5% of residues in the sintering mix. The raw material characterization indicated that using up to 50% of residues in the sintering mix does not sensibly alter the distribution of particle types (nucleating, adherent, etc.) of the mixes as compared to a mixture without residues. Appreciable iron and carbon contents could also be found in the residues, which are advantageous for the sintering process. It could be seen that, though they contain more zinc than the sinter feed, residues have comparable or better chemical properties than the latter. Amongst these, the increased total iron content and lower content of silica stood out. The high temperature tests indicated that recycling 100% of an integrated steel mills residue generation through the sintering route produces sinter with identical chemical and mineral properties to a sinter produced with no residues at all. Increases in zinc content and a higher wustite content (which is less reducible) were observed only beyond 25% residues content in the sintering mix, which is unattainable with the typical generation rates of metallurgical residues. The multicomponent thermodynamic equilibrium model gave out coherent predictions of the chemical composition and mineral phases when compared to the experimental results, especially for elements such as cadmium, chromium and lead, which are volatilized in the sintering process, and for slag components such as CaO, MgO, SiO2 and Al2O3. There were quantitative differences between experimental results and model predictions for the partition of components which are subject to oxidation and reduction reactions, such as iron, zinc and alkali. These differences were attributed to the important kinetic limitations of the actual sintering process, which takes place in non-equilibrium conditions. Nevertheless, the model was coherent in predicting the formation of hematite, magnetite, wustite and dicalcium silicate for the high temperature tests, both for the heating and cooling steps of the process, which take place in atmospheres with different oxygen potentials. The results of the research indicated that there are no appreciable impacts of using residues, be it on the product sinter chemistry, on the size distribution of sintering mixes or on the estimated blast furnace charging of harmful elements such as zinc, alkali, heavy metals or Sulphur. Therefore, the conclusion is that there is space, in ironmaking, for increasing residue recycling proportions through the sintering process